Injection therapy in tendinopathies – What's (new) and what's behind all this? Injektionstherapie bei Tendinopathien – Was gibt es (Neues) und was steckt eigentlich dahinter? - Hotfiel, T.; Hirschmüller, A.; Engelhardt, M.; Grim, C.; Tischer, T.; Pachowsky, M. (Sport-Orthopädie, Sport-Traumatologie, 2024)
Tendinopathies are one of the most common and challenging injuries in sports. Beside others, the injection therapy is an established procedure in the treatment of tendinopathies. A large number of different pharmaceutical agents are available. The present review provides a overview on commonly applied agents ephazizing it's molecular mechanism, side effects and clinical implications. With special focus on future directions innovative agents are included and discussed as well.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Biologica; Injection Therapy; PRP; Steroids; Tendon Injuries